Zoneamento de susceptibilidade a escorregamentos planares na bacia do rio Neverí - Venezuela - Pineda, María José Entrena (2017)
The present work has a general objective to realize a zoning of susceptibility to landslides applied in the Neverí river basin, in the Anzoátegui and Sucre states, Venezuela. The choice of the study area is justified by the fact that it is a natural unit, where the dam of Turimiquire and the capital of Anzoátegui state (Barcelona) is located. Studies of geological, geomorphological aspects; Topographic, hydrological, allow to know the natural phenomena that can affect a population, locating the threat and the susceptibility in a geographic space. Therefore, it is necessary to associate those variables whose information complements each other to be able to produce information, in which the behavior that will have an area determined before any intervention is identified, that is, the need to produce a relative stability zoning, where Can be represented through a scale of intensities the levels of susceptibility. The development of investigations into the risks within the geographical discipline arises with a fundamentally applied character in relation to the various aspects that involve the classification of the territory and as a consequence of the increasingly common occurrence of natural phenomena with devastating effects , Anywhere in the world. The bibliographic review of the present work presents its bases starting from the systemic approach, geoenvironmental studies and the use of geographic information systems environments for the use of geoprocessing tools. The methodology adopted is part of a geoenvironmental characterization in combination with the application of the model of susceptibility to landslides proposed by Jiménez (2012), which performs a combination of factors conditioning slippages and additionally under the same assumptions propose a morphometric - structural model and were generated Two scenarios that allow to establish criteria to realize the zoning susceptibility to landslides. The results were satisfactory in the application of both models in the basin where the susceptibility to planar landslides was obtained in classes of very low, low, moderate, high and very high susceptibility.